Effect of Osteoblast‐Specific Deletion of the Proton Receptor OGR1. (31st October 2022) - Krieger, Nancy S; Chen, Luojing; Becker, Jennifer; Chan, Michaela; Bushinsky, David A
ABSTRACT: Metabolic acidosis (MET) stimulates bone resorption through inhibition of osteoblast (OB) bone formation and stimulation of osteoclast (OC) bone resorption. We found that OGR1, a G protein‐coupled proton (H + )‐sensing receptor, was critical for initial H + signaling in the OB. In mice with a global deletion of OGR1, we demonstrated that loss of OGR1 impairs H + ‐induced bone resorption, leading to increased bone density through effects on both the OB and OC. Using an OC‐specific deletion of OGR1, we found that MET directly activates OGR1 in the OC. To determine if the response of OGR1 to MET in the OB is independent of a response in OCs and to characterize direct activation of OGR1 in the OB, we studied female mice with an OB‐specific deletion of OGR1 (OB‐cKO) and differentiated osteoblasts derived from marrow of OB‐cKO and wild‐type (WT) mice. In OB‐cKO mice, we found increased bone area in both tibial and femoral cortical bone. Specific loss of OB OGR1 increased in vitro mineralization, alkaline phosphatase activity, and expression of osteoblast‐specific genes compared with WT with no alteration in OC activity. MET stimulation of OB cox2 and fgf23 gene expression was inhibited in OB‐cKO OB. These results indicate that MET activation of OGR1 in the OB is independent of the response in the OC and that OGR1 in both cell types is required for a complete response to MET. Characterization of the role of OGR1 in MET‐induced bone resorption will improve our understanding of bone loss associated with metabolic acidosis in patients with chronic kidney disease. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.